2021
DOI: 10.1038/s41419-021-03562-6
|View full text |Cite
|
Sign up to set email alerts
|

Protectin DX restores Treg/Th17 cell balance in rheumatoid arthritis by inhibiting NLRP3 inflammasome via miR-20a

Abstract: Regulatory T-cell (Treg)/T-helper 17 (Th17) cell balance plays an important role in the progression of rheumatoid arthritis (RA). Our study explored the protective effect of protectin DX (PDX), which restored Treg/Th17 cell balance in RA, and the role of the nucleotide-binding domain (NOD)–like receptor protein 3 (NLRP3) inflammasome pathway in this process. Using mass spectrometry, we discovered that level of PDX decreased in active-RA patients and increased in inactive-RA patients compared with HCs, and seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 42 publications
1
35
1
Order By: Relevance
“…These data suggested that NLRP3 inflammasome might participate in the regulation of Treg/Th17 cell balance in autoimmune diseases. In a recent study, Jin et al confirmed that protect in DX (PDX) could restore Treg/Th17 cell balance in RA by inhibiting NLRP3 inflammasome via miR-20a ( Jin et al, 2021 ). Considering that the NLRP3 inflammasome plays an important role in the Treg/Th17 cell balance, which in turn regulates autoimmunity, we speculated that YH treatment alleviated autoimmune thyroiditis in rats, which could be due to the Th17/Treg rebalancing regulated by Wnt/β-catenin pathway through NLRP3 inflammasome deactivation ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…These data suggested that NLRP3 inflammasome might participate in the regulation of Treg/Th17 cell balance in autoimmune diseases. In a recent study, Jin et al confirmed that protect in DX (PDX) could restore Treg/Th17 cell balance in RA by inhibiting NLRP3 inflammasome via miR-20a ( Jin et al, 2021 ). Considering that the NLRP3 inflammasome plays an important role in the Treg/Th17 cell balance, which in turn regulates autoimmunity, we speculated that YH treatment alleviated autoimmune thyroiditis in rats, which could be due to the Th17/Treg rebalancing regulated by Wnt/β-catenin pathway through NLRP3 inflammasome deactivation ( Figure 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…The balance between Tregs and Th17 is the key point in the maintenance of immune homeostasis. Similarities to that of other ADs, such as systemic lupus erythematosus and autoimmune hepatitis, the pathogenesis of RA has been observed to involve an imbalance between Tregs and Th17 (Jin et al, 2021). The inflammatory cytokine environment is a key driver that could globally push Tregs/Th17 toward imbalance because the combination of TGF-β and IL-6 allows T-cell differentiation toward the Th17 phenotype, whereas if TGF-β is present alone, T cells will differentiate or revert into iTregs in vitro (Bettelli et al, 2006).…”
Section: Mechanisms Of Impaired Function Of Tregsmentioning
confidence: 64%
“…Of interest, in the last years, lipidomic analysis of plasma or serum recovered from patients with chronic inflammatory disorders implicating pathogenic T-cell responses constantly showed decreased SPM concentrations at the time of active disease, compared with healthy and/or inactive disease status. This was reported for MaR1 and PD1 in rheumatoid arthritis (RA) (59,85) and for RvD1 in SLE, MS, and chronic heart failure (63,83,84). Lower levels of RvD3, RvD4, and RvE3 were also observed in a small cohort of stage III RA patients, with concomitant increase in inflammatory TBX2 (86).…”
Section: Defective Pro-resolving Pathways Associated With Pathogenic T-cell Responsesmentioning
confidence: 66%